Structural and electrochemical properties of babassu coconut mesocarp-generated activated carbon and few-layer graphene. (April 2019) - Ghosh, Anupama; Razzino, Claudia do Amaral; Dasgupta, Archi; Fujisawa, Kazunori; Vieira, Laís Helena S.; Subramanian, Shruti; Costa, Rubens S.; Lobo, Anderson O.; Ferreira, Odair P.; Robinson, Joshua; Terrones, Mauricio; Terrones, Humberto; et al.
Abstract: Activated Carbon (AC) with high specific surface area and elevated porosity was synthesized from babassu mesocarp by hydrothermal carbonization, followed by KOH activation-coupled pyrolysis and subjected to heat-treatment at three different temperatures to generate AC-1100, AC-1400 and AC-2200. Raman spectroscopy, X-Ray diffraction (XRD), transmission electron microscopy (TEM) and N2 adsorption-desorption were used to characterize structurally the synthesized materials and electrochemical studies to evaluate the capacitance properties. The Raman spectra showed sharpening of graphitic bands and decrease in intensities of amorphous bands with the increase of treatment temperature. AC-2200 showed a significant decrease of ID /IG due to the crystal growth in ab plane and drastic increase of I2D /IG due to graphitic ordering in c direction, further proven by sharpening of characteristic XRD peaks and visualization of few-layer well-formed graphite micro-crystals by TEM. Although gradual heat treatment resulted in an increase in sample crystallinity, the surface area and porosity decreased, leaving AC-2200 practically non-porous. These changes were reflected in their electrochemical properties as AC-1400 showed highest double layer capacitance owing to an optimization between structural ordering and retention of porosity, while the capacitance, as well as the resistance, of AC-2200, decreases dramatically due to loss of pores and increased crystallinity brought in by graphitization. Graphical abstract: Image 1